2009
DOI: 10.1097/ijg.0b013e31818624a4
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Optic Nerve Head Drusen

Abstract: Objective-To demonstrate a new algorithm that can determine the shape, location, and volume of optic nerve head drusen (ONHD) which were imaged with spectral domain optical coherence tomography (SDOCT).Methods-One exenteration patient and four glaucoma patients with bilateral ONHD were recruited from the Massachusetts Eye and Ear Infirmary and from a private practice office. Images were obtained using an experimental SDOCT system developed at the Wellman Center for Photomedicine, Massachusetts General Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…Various ancillary tests, including B-scan ultrasonography, 55; 105; 151; 168 fundus autofluorescence, 95; 140; 145 orbital computed tomography (CT) scan, 12; 131; 162 fluorescein angiography (FA), 24; 159; 177 scanning laser ophthalmoscopy, 75; 103; 187 electrophysiology, 17; 18; 23; 142; 186 and more recently optical coherence tomography (OCT), 31; 88; 112; 125; 215 have been used to identify optic disc drusen. These tests may be less useful in children who typically have buried drusen that are more difficult to detect.…”
Section: Diagnostic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various ancillary tests, including B-scan ultrasonography, 55; 105; 151; 168 fundus autofluorescence, 95; 140; 145 orbital computed tomography (CT) scan, 12; 131; 162 fluorescein angiography (FA), 24; 159; 177 scanning laser ophthalmoscopy, 75; 103; 187 electrophysiology, 17; 18; 23; 142; 186 and more recently optical coherence tomography (OCT), 31; 88; 112; 125; 215 have been used to identify optic disc drusen. These tests may be less useful in children who typically have buried drusen that are more difficult to detect.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…5; 31; 50; 76; 88; 93; 104; 112; 114; 135; 195; 211; 215 On OCT, optic disc drusen can be seen as a focal hyperreflective mass posterior to the outer plexiform and outer nuclear layers, with absence of the inner and outer segment photoreceptor junction (Figure 5); 112 however, Kulkarni et al found standard spectral-domain OCT (SD-OCT) to be unreliable at distinguishing between buried optic disc drusen and true optic disc edema in children and young adults. 104 They noted that, in several cases of mild disc edema, OCT showed nonspecific hyperreflective areas underneath the optic nerve that were confused with drusen.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…20 The only previous report of drusen quantification in OCT was performed by Yi et al in a study which used an experimental SD-OCT device. 22 …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the only study which has attempted to quantify the size, shape, and location of ONHD used an experimental SD-OCT instrument. 22 Therefore, this study sought to determine if SS-OCT volume scans could be used to measure ONHD size, shape, and location.…”
Section: Introductionmentioning
confidence: 99%
“…While this technique shows promise, it seems most effective in cases where surface ODD are clinically apparent; in more subtle cases, the distinguishing OCT features are less clear. Buried ODD can be detected with spectral-domain OCT (8), but differentiating ODD from ODE has yet to be established with this technique.…”
Section: Discussionmentioning
confidence: 99%